Recognizing culture based religious icons from muslim culture user interface design (MCUID) prototype - Nasruddin, Zan Azma; Hussin, Husnayati (2014)
Ever since Allah has used metaphor to send His messages to mankind through Al Quran. Inspired from it, this study is to examine how metaphor could be integrated in the interface design. The phenomena nowadays, numbers of metaphor worlds and their participants that growing rapidly, primarily is a Western Culture dominated environment. Attention paid to other culture is still very little. The study examines this issue from an Islamic perspective. There is an assumption that if metaphor worlds are to become a truly global platform for users then it will be essential to "encode" the flexibility for social interactions to take place in a way that is sensitive to other cultures and most important matters that could give values to the target users. The key concern is to shift the focus of development from standard interface design to Islamic interface design. A framework has been developed adapted from Culture Centered Design. Important features have been added to the framework especially on Islamic values as a way of life and a journey towards Allah. Furthermore, an interface prototype known as Muslim Centered User Interface Design (MCUID) is created. Empirical investigation through evaluating the prototype has been done to tabulate the patterns on how Muslim users’ perceptions towards recognizing culture based religious icons in MCUID prototype. The findings are analyzed using Atlas.ti 7 both in qualitative and quantitative measurements.